Reduction Of Membrane Fouling Using Helical Baffles For Crossflow Microfiltration - Mariadas, Anthony (2003)
The objectives of this research is investigate the use of helical baffles as a hydrodynamic for reducing membrane fouling and enhancing the flux. Experiments were conducted using ceramic, tubular membranes and using Ti02 suspensions and Bakers yeast solutions as the feed. The optimum configurations of helical baffles in respect to the geometry were explored. The effect of operating parameters such as different Transmembrane pressure, different feed concentrations, different shape of membrane inner surface, long hour experiments and the effect of different types of feed on flux were also conducted.